Hybrid anonymous channel for recipient untraceability via SDN-based node obfuscation scheme - Hui ZHAO; Liangmin WANG (Tongxin xuebao)
Leveraging the advantages of software defined networking (SDN),a new anonymous communication solution was de-signed for recipient untraceability.An obfuscation scheme in SDN domain was proposed to build a hybrid anonymous channel to solve the problem of large and highly variable delays and download time when using existing anonymous com-munication system such as Tor.The hybrid anonymous channel concatenated two sender anonymous channels in Tor and SDN to provide both sender and receiver anonymity.Adversaries can trace smaller portions of the path in hybrid channel.Experimental results show that the hybrid channel is as anonymous as two connected Tor circuits,with only a small larger latency (15%) compared with Tor.